Diseño de un sistema de gestión de seguridad y salud en el trabajo en una empresa de servicio de consultoría ambiental - Amado Cuadros, Luis Alberto (2016)
Tecandina S.A. is a Peruvian company that develops environmental consultant work in the mining subsector; has 12 workers in its office and hires professionals specialized in mining and environmental issues for their projects. Administrative labors are done in Lima, while the necessary fieldwork to gather information is performed in areas where mining projects are located, mostly in the highlands of Peru. The main objective of this research is to design a Work Safety and Health Management System (OHSMS), that allows Tecandina S.A. to carry out its implementation, verification and control; to achieve this goal , an analysis of the external and internal environment of the company was performed; the company´s current situation diagnose (baseline) related with safety and health at work; and finally the cost involved in implementing and maintaining OHSMS was calculated.